Developing cultural awareness in Ethics in Hungary - Fenyődi, Andrea (Gyermeknevelés Tudományos Folyóirat, 2022)
In Hungary, the 2012/13 academic year saw the introduction of Ethics [etika], a newly designed subject, into the national curriculum for primary education. Aiming to promote learners’ understanding of individual and social values by means of its subject-matter covering major aspects of the world of human relations, Ethics both directly and indirectly teaches about culture. This paper gives an insight into the character and implementation of the subject while presenting some practical ideas regarding how to develop primary children’s cultural awareness. My analysis contends that the weekly Ethics lesson accomplishes this goal by providing a discursive approach for students to reflect on their personal experience or any knowledge gained in other school subjects. Students can form and express their opinions about news, current events, human behaviour or analyse their own personal dilemmas or genuine conflicts. The variety of the methodological tools promotes learning about culture both implicitly and explicitly from a young age while enabling learners to practise the skills that are needed for displaying cultural sensitivity.